Outcome of Juvenile Idiopathic Arthritis Associated Uveitis in Two Disease Subtypes - Dragana LAZAREVIĆ; Ivana NIKOLIĆ; Marija RATKOVIĆ-JANKOVIĆ; Jelena VOJINOVIĆ (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the efficacy of adalimumab as a first line biologic agent in specific subtypes of juvenile idiopathic arthritis (JIA) patients with associated uveitis. Patients and Methods: We retrospectively analyzed the data of 11 JIA patients (8 males, 3 females; mean age 14.5 years; range 9 to 18 years) with associated uveitis treated with biologic therapy. All patients were diagnosed as oligoarticular/extended oligoarticular or enthesitis-related JIA subtypes, treated with methotrexate, and had active or previous history of uveitis for which adalimumab was prescribed. We tested all patients for anti-nuclear antibody presence and human leukocyte antigen genotype. We assessed disease activity and therapy efficacy by American College of Rheumatology 50%, 70%, and 100% improvement criteria. We evaluated uveitis activity by slit-lamp biomicroscopy and recorded adverse events. Results: Of the JIA patients, three (27.27%) had oligoarticular/extended oligoarticular JIA and eight (72.73%) had enthesitis-related arthritis. Anti-nuclear antibody positivity was present in 27.27% (all females) while human leukocyte antigen-B51 was determined in 62.5% and human leukocyte antigen-B27 in 12.5% of patients. Mean uveitis duration before adalimumab introduction was 12.3 months. After two years of follow-up, there were no relapses of uveitis and visual acuity was stable while on adalimumab and methotrexate treatment. All patient were gradually tapered and discontinued treatment with topical steroids. Disease activity improved and seven patients (63.64%) achieved American College of Rheumatology 100% response rate (attained remission), while four patients (36.36%) achieved American College of Rheumatology 70% response rate. Conclusion: Anti-nuclear antibody positivity with oligoarticular/extended oligoarticular and enthesitis-related arthritis JIA subtypes, which are known for their high risk to develop uveitis, may benefit from adalimumab as a first line anti-tumor necrosis factor agent.